The February Revolution of 1917 and the Fate of Prisoners of the First World War - S. I. Chernyavskiy (Международная аналитика, 2016)
The First World War put a number of practical issues before the Russian diplomats. The first one was sending home Russian citizens stranded in foreign countries, and the second, helping numerous prisoners. Total 1.451.160offoreign prisoners of war was registered in Russia, and in enemy countries, 2.501.250Russians.After the February Revolution, the scope of activities of Russian MFA foreign institutions expanded significantly. Diplomats were to ensure the repatriation of political refugees, among which dominated either monarchical or revolutionary sentiments. The Provisional Government has sought to drop on the Ministry, as much as possible, all the complex issues related to discrimination between desirable and non-desirable returnees.After the October Revolution of 1917 under the Treaty of the Armistice between Russia and Bulgaria, Germany, Austria-Hungary and Turkey 2 (15) in December 1917 and the agreement between Russia and Germany, Austria-Hungary, Bulgaria and Turkey from March 3, 1918, prisoners of both sides had to be exchanged and sent home.The number of Russian prisoners of war by the middle of 1917 was 2.417.000. Until 1918 in Russia came from captivity 715.000 people with disabilities and 60.000 fled from the camps. At the beginning of 1918 in captivity were 1.642.000 (68 %). Except 190.000 died in captivity, 95.000 remained in Europe, 215.000 have returned to the Baltic States. Thus, 500.000 (21 %), Russian prisoners of war did not return to Russia.Issues of humanitarian cooperation are still the focus of the Russian Ministry of Foreign Affairs. Russia is making a worthy contribution to the work of the Office of the UN High Commissioner for Refugees and the International Organization for Migration, cooperates with the Council of Europe and the OSCE.